2004
DOI: 10.1590/s1806-37132004000600007
|View full text |Cite
|
Sign up to set email alerts
|

Dispnéia crônica e alterações funcionais respiratórias em ex-trabalhadores com asbestose avaliados para concessão de benefício

Abstract: INTRODUÇÃO: A dispnéia é um sintoma de difícil avaliação, principalmente nas doenças ocupacionais. OBJETIVO: Avaliar a relação entre presença e intensidade de dispnéia crônica, e sua repercussão funcional em ex-trabalhadores com asbestose na avaliação de disfunção e incapacidade. MÉTODO: Escores de dispnéia pelas escalas Medical Research Council modificada, American Medical Association de 1984 e 1993 e Baseline Dyspnea Index foram obtidos em 40 ex-trabalhadores com diagnóstico de asbestose, os quais foram tamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…In a study involving former workers with asbestosis, (19) smoking was not associated with severe respiratory symptoms, principally dyspnea. However, most studies have reported an association between severe respiratory symptoms and smoking, which is an aggravating factor for occupational respiratory diseases.…”
Section: Discussionmentioning
confidence: 91%
“…In a study involving former workers with asbestosis, (19) smoking was not associated with severe respiratory symptoms, principally dyspnea. However, most studies have reported an association between severe respiratory symptoms and smoking, which is an aggravating factor for occupational respiratory diseases.…”
Section: Discussionmentioning
confidence: 91%
“…É importante ressaltar que a reprodutibilidade interobservador da escala IDB foi descrita previamente em nosso meio 13 . Além disso, diversos estudos publicados, no Brasil e no exterior, fizeram uso de ambas as escalas citadas, confirmando sua utilização como instrumento para avaliação da dispneia basal e da dispneia pósintervenções [25][26][27][28][29] .…”
Section: Discussionunclassified
“…Although simple in design and analyses, they played a relevant role in demonstrating that in Brazil, asbestos also caused health problems. Other case studies were based on compensation benefits granted by the Social Insurance Institute [ 67 , 72 ].…”
Section: Epidemiology and Prevention Of Asbestos-related Diseases mentioning
confidence: 99%